Ultrasound-enhanced systemic thrombolysis for acute ischemic stroke. - Alexandrov, A; Molina, C; Grotta, J; Garami, Z; Ford, SR; Alvarez-Sabin, J; Montaner, J; Saqqur, M; Demchuk, A; Moyé, L; Hill, MD; Wojner, A (2004)
BACKGROUND: Transcranial Doppler ultrasonography that is aimed at residual obstructive intracranial blood flow may help expose thrombi to tissue plasminogen activator (t-PA). Our objective was to determine whether ultrasonography can safely enhance the thrombolytic activity of t-PA. METHODS: We treated all patients who had acute ischemic stroke due to occlusion of the middle cerebral artery with intravenous t-PA within three hours after the onset of symptoms. The patients were randomly assigned to receive continuous 2-MHz transcranial Doppler ultrasonography (the target group) or placebo (the control group). The primary combined end point was complete recanalization as assessed by transcranial Doppler ultrasonography or dramatic clinical recovery. Secondary end points included recovery at 24 hours, a favorable outcome at three months, and death at three months. RESULTS: A total of 126 patients were randomly assigned to receive continuous ultrasonography (63 patients) or placebo (63 patients). Symptomatic intracerebral hemorrhage occurred in three patients in the target group and in three in the control group. Complete recanalization or dramatic clinical recovery within two hours after the administration of a t-PA bolus occurred in 31 patients in the target group (49 percent), as compared with 19 patients in the control group (30 percent; P=0.03). Twenty-four hours after treatment of the patients eligible for follow-up, 24 in the target group (44 percent) and 21 in the control group (40 percent) had dramatic clinical recovery (P=0.7). At three months, 22 of 53 patients in the target group who were eligible for follow-up analysis (42 percent) and 14 of 49 in the control group (29 percent) had favorable outcomes (as indicated by a score of 0 to 1 on the modified Rankin scale) (P=0.20). CONCLUSIONS: In patients with acute ischemic stroke, continuous transcranial Doppler augments t-PA-induced arterial recanalization, with a nonsignificant trend toward an increased rate of recovery from stroke, as compared with placebo.